The relationship between taste and status conspicuous consumption - Yuliia Skladan (Cхід, 2018)
This research starts with the analysis of conspicuous consumption as a specific means to emphasize one’s social status. As far back as the end of the 19th century Thorstein Veblen developed a theory about a specific class who was characterized by nonproductive activities and specific surrounding - servants, clothing, which is not suitable for work, luxurious furniture. Since that idea was examined many times in various researches during the last century, it appears to be interesting to compare it with the concept of taste, which one cannot help appealing to while choosing anything, especially something that shows one’s status.